(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The link between the mean annual temperature and the mean temperature in July of the water of the rivers has been investigated. Linear equations of their link have been made for this purpose for the rivers having different feeding and for all hydrological regions of the Republic of Armenia. They are of great practical importance and can be used to determine the mean annual water temperature of the rivers which are poorly investigated or not investigated at all.